Inducing uniform single-crystal like orientation in natural rubber with constrained uniaxial stretch. Issue 25 (7th July 2015) - Zhou, Weiming; Meng, Lingpu; Lu, Jie; Wang, Zhen; Zhang, Wenhua; Huang, Ningdong; Chen, Liang; Li, Liangbin
<x xml:space="preserve">Abstract</x> The single-crystal-like orientation of natural rubber polycrystals is induced by constrained stretch, and the free energy of the final state should be incorporated into the thermodynamic driving force for flow-induced crystallization.